1985
DOI: 10.1007/bf03186266
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and ovipositional behaviour in some reduviids (Insecta-Heteroptera)

Abstract: Feeding behavioural studies of many exclusivelypredatory species exhibit c1earcut stimuli-response mediated sequences and these can be categorised into distinct sub-units like: search and location of prey ....approach and attack: of prey ....immobilisation of prey ....transportation of prey to safe place ....consumption of prey. These feeding behavioural activities differ among reduviids particularly with respect to prey types. These bugs are endowed with many structural, physiological and behavioural adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…It is likely that these white or off-white setae reflect sunlight and prevent overheating of this insect in bright sunshine. The narrow and elongate body of this bug makes it difficult to locate this animal on slender stems of Capparis, and perhaps also on grasses, where they are reported to be present (Haridass 1985). The dense covering of setae may provide additional camouflage.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is likely that these white or off-white setae reflect sunlight and prevent overheating of this insect in bright sunshine. The narrow and elongate body of this bug makes it difficult to locate this animal on slender stems of Capparis, and perhaps also on grasses, where they are reported to be present (Haridass 1985). The dense covering of setae may provide additional camouflage.…”
Section: Discussionmentioning
confidence: 96%
“…The bionomics of all species of Rhaphidosoma has remained poorly known, and no published information is available on their prey, oviposition and egg structure except that of Rh. atkinsoni by Haridass (1985Haridass ( , 1988 and some observations on the African congeners by Miller (1953Miller ( , 1956.…”
Section: Introductionmentioning
confidence: 96%
“…Four less specific observations by Miller (1953) indicated that ectrichodiines targeted trunk intersegmental membranes, and Lawrence (1984) mentioned intersegmental membranes without reference to body region. Haridass (1985) stated that ectrichodiines also insert stylets at the head-collum intersegmental membrane. In our two laboratory trials, specimens of R. cinctiventris inserted stylets at the headcollum intersegmental membrane and/or at intersegmental membranes along the ventral, ventro-lateral, and/or dorsal trunk (Fig.…”
Section: Point Of Stylet Insertionmentioning
confidence: 99%
“…It is also unknown if Ectrichodiinae target the body regions that possess defensive glands to sequester their own defensive compounds, or if they avoid the millipedes' defense glands. In addition, predation in Ectrichodiinae may be a communal activity (Haridass & Ananthakrishnan, 1980;Haridass, 1985) rather than a solitary behavior as usually observed in Reduviidae (Readio, 1927;McMahan, 1983;Li et al, 2010), but details on this unusual subsocial behavior are scarce.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation